AKUNTANSI SEBAGAI PEMBENTUK MITOS (Studi Fenomenologi Pada Penggunaan Angka Akuntansi Sebagai Penilai Kinerja) - Putu Premadi, Ignatius; Chariri, Anis (Diponegoro Journal of Accounting, 2013)
This research is about the myths that are believed by the phenomenom of accounting research users caused by accounting process. Focus of this study is an analysis of we use accounting numbers in the budget as a performance appraisal at Diponegoro University. This study aims to analyze how members of the organization understand the meaning of governmental accounting; analyze how budgets are used as performance apparsial in the public sector organizations, and alayze accounting aspects that shape editorial team of assessors have behavior in the assessment of the budget in the public sector organizations.This study uses a phenomenological study on interview result data. The data analyzed is the interreview result with the editorial team of assessors and budgeting at University of Diponegoro in 2012. The data obtained from through direct interview process. At the end of this study can be concluded that the accounting from a myth that is trustes, belived and carried out by the assessment from budgeting. It is shown from understanding of accounting member organizarions from literative communication process, so an understanding of the organizations member about understanding the meaning of accounting based on the habbit in work filed. Besides the use of the budget as a benchmark for assessing performance is not in accordance with the rules, but because of habit and events that have happened over use budget for assess performance already belived and trusted to fit the needs of the organization.